Różnorodność biologiczna jako atrakcja turystyczna - Zielińska, Anetta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Biodiversity is significant for tourists and tourist industry. Each part of biodiversity is a very important element of tourist product (according to the region - national or sightseeing parks, as well as according to linear aspects - tourist paths, sightseeing stands, banks of genes) or independent tourist stand. There is a strong correlation between biodiversity and tourist attraction, which shows that the increase of biodiversity causes an increase in tourist attractiveness of the region. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 183-189